PENGEMBANGAN VIDIO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD PADA MATA PELAJARAN IPAS - Nurjumiati, Nurjumiati; Rohimat, Rohimat; Yulianci, Syahriani; Hardianingsih, Sri; Nurhairunnisah, Nurhairunnisah (Jurnal Kependidikan, 2025)
This study aims to: (1) Test the feasibility of animated video media in improving student learning outcomes. (2) Test the practicality of animated video media in improving student learning outcomes. (3) Test the effectiveness of animated video media in improving student learning outcomes. This animated video was compiled using the ADDIE model research and development method.. The level of feasibility of the animated video was obtained from the media expert validator and the material expert validator who were analyzed and obtained the standard gain value and criteria for determining effectiveness as an increase in student learning outcomes. The results of this study are as follows: (1) Animated Video Media has been produced that is suitable for use, reviewed from the assessment of suitability by the material validator, namely 90% with the category (very suitable) and the media validator obtained a score of 84.7% (very suitable) to improve the science learning outcomes of grade IV elementary school students; (2) The practicality of animated video media with the category (very practical) with a score of 93.5; (3) the increase in the effectiveness of students' science learning through Animated Video Media is 70 with the moderate category.